Obesity, High Blood Pressure, and Physical Activity Determine Vascular Phenotype in Young Children: The EXAMIN YOUTH Study. Issue 1 (January 2019) - Köchli, Sabrina; Endes, Katharina; Steiner, Ramona; Engler, Luca; Infanger, Denis; Schmidt-Trucksäss, Arno; Zahner, Lukas; Hanssen, Henner
Abstract : Cardiovascular disease often develops during childhood, but the determinants of vascular health and disease in young children remain unclear. The study aimed to investigate the association of obesity and hypertension, as well as physical fitness with retinal microvascular health and large artery stiffness, in children. In this cross-sectional study, 1171 primary school children (aged 7.2±0.4 years) were screened for central retinal arteriolar equivalent (CRAE) and central retinal venular equivalent (CRVE) diameters, pulse wave velocity (PWV), body mass index, blood pressure (BP), and cardiorespiratory fitness by standardized procedures for children. BP was categorized according to the reference values of the population-based German KiGGS study (Kinder- und Jugendgesundheitssurvey [Children- and Adolescents Health Survey]) and the American Academy of Pediatrics guidelines. Overweight (mean [95% CI]: CRAE, 200.5 [197.9–203.2] µm; CRVE, 231.4 [228.6–234.2] µm; PWV, 4.46 [4.41–4.52] m/s) and obese children (CRAE, 200.5 [196.4–204.7] µm; CRVE, 233.3 [229.0–237.7] µm; PWV, 4.51 [4.43–4.60] m/s) had narrower CRAE, wider CRVE, and higher PWV compared with normal-weight children (CRAE: 203.3 [202.5–204.1] µm, P <0.001; CRVE: 230.1 [229.1–230.9] µm, P =0.07; PWV: 4.33 [4.31–4.35] m/s, P <0.001). Children with high-normal BP (CRAE, 202.5 [200.0–205.0] µm; PWV, 4.44 [4.39–4.49] m/s) and BP in the hypertensive range (CRAE, 198.8 [196.7–201.0] µm; PWV, 4.56 [4.51–4.60] m/s) showed narrower CRAE, as well as higher PWV, compared with normotensive peers (CRAE: 203.7 [202.9–204.6] µm, P <0.001; PWV: 4.30 [4.28–4.32] m/s, P <0.001). With each unit increase of body mass index and systolic BP, CRAE decreased and PWV increased significantly. Children with the highest cardiorespiratory fitness had wider CRAE, narrower CRVE, and lower PWV compared with least fit children. Childhood obesity and hypertension, even at preclinical stages, are associated with microvascular and macrovascular impairments in young children. Primary prevention programs targeting physical activity behavior may have the potential to counteract development of small and large vessel disease early in life. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02853747. Abstract : Supplemental Digital Content is available in the text.